Transforming agriculture for improving food and nutrition security among Nigerian farm households - Ecker, Olivier; Hatzenbuehler, Patrick L.; Mahrt, Kristi (International Food Policy Research Institute, 2018)
The release by the Nigerian Federal Ministry of Agriculture and Rural Development (FMARD) of the Agricultural Transformation Agenda (ATA) in 2010 and its successor strategy document, the Agriculture Promotion Policy (APP), in 2016 as official policy strategy documents signals a shift in policymaker attention toward improving the performance of the agricultural sector in the country after decades of neglect. This paper discusses the potential effects of changes in agricultural production practices due to these adjustments in strategy on food consumption, and, hence, on food security and nutrition in Nigeria. We outline the theoretical linkages between changes in agricultural production patterns by farm households and their food consumption decisions.